EFFECT OF BANANA, APPLE, AND PINEAPPLE ON SEX HORMONES IN MALE WISTAR RATS TREATED WITH MONOSODIUM GLUTAMATE - Gbaranor K. B; Tamuno-Opubo A; Olatunbosun, T. H; Saronee F; Okari A. K; AlexanderUloghoman E; Biibaloo L. L; Ovili-Odili B. Z; Chris-Biriowu H; Odimabo M; Otto B. J.; Krukru E. E (Scholar Express Journals, 2025)
Sex hormones are important in developing and maturation of sex cells. In male, the sex hormone is testosterone and this hormone is produced by the testes with control from the hypothalamus through the release of gonadotropin releasing hormone (GnRH). The hormone testosterone promotes spermatogenesis in male and thus enhance reproductive process in male. Fruits combination is well eaten across the world and it increases sperm parameters. The study aimed to evaluate the Effect of Banana, Apple, and Pineapple on Sex Hormones in Male Wistar Rats Treated with Monosodium Glutamate. The study involved 30 Male Wistar rats (weighing 130-180g) randomly selected into five groups with 6 rats per group. Group 1 – Control, Group 2, 3 and 4 were administered with 1ml, 2mls and 3mls of smoothies respectively, Group 5 – Monosodium glutamate (400mg/ml), and Group 6 – Monosodium glutamate + High dose (400mg/ml +3mls of smoothies). Results from this study showed that smoothies administration in rats increase in testosterone. The study shows smoothies decreased total cholesterol below control concentrations of 3.45±0.26 mmol/L, to 3.15±0.43mmol/L, 2.90±0.06mmol/L and maximally 2.80±0.17 mmol/L at 3ml/kg dose dependently. On the contrary, MSG raised total cholesterol levels to 3.40±0.12 mmol/L, although combination treatment with high-dose smoothies reduced total cholesterol further to 2.40±0.06 mmol/L (p <0.05). Hence, smoothies mitigated the hypercholesterolemic effect of MSG cotreatment.>
Keywords: Banana; Apple; Pineapple Sex Hormones